2011
DOI: 10.1101/gr.126417.111
|View full text |Cite
|
Sign up to set email alerts
|

Tissue type is a major modifier of the 5-hydroxymethylcytosine content of human genes

Abstract: The discovery of substantial amounts of 5-hydroxymethylcytosine (5hmC), formed by the oxidation of 5-methylcytosine (5mC), in various mouse tissues and human embryonic stem (ES) cells has necessitated a reevaluation of our knowledge of 5mC/5hmC patterns and functions in mammalian cells. Here, we investigate the tissue specificity of both the global levels and locus-specific distribution of 5hmC in several human tissues and cell lines. We find that global 5hmC content of normal human tissues is highly variable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
294
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(346 citation statements)
references
References 51 publications
37
294
3
5
Order By: Relevance
“…35 While 5-hmc is an intermediate in active DNA demethylation, 5-mc and 5-hmc levels are not inherently correlated 36 and therefore our observations of decreased 5-mc and 5-hmc are not contradictory. Furthermore, our results could also be the product of the direct role of 5-hmc in RNA splicing 37 and gene expression through inhibition of chromatin remodelling 38 , which may offer an alternative explanation for our observations.…”
Section: Discussionmentioning
confidence: 70%
“…35 While 5-hmc is an intermediate in active DNA demethylation, 5-mc and 5-hmc levels are not inherently correlated 36 and therefore our observations of decreased 5-mc and 5-hmc are not contradictory. Furthermore, our results could also be the product of the direct role of 5-hmc in RNA splicing 37 and gene expression through inhibition of chromatin remodelling 38 , which may offer an alternative explanation for our observations.…”
Section: Discussionmentioning
confidence: 70%
“…5hmC enrichment within the H19 gene body was also analyzed since previous studies have identified the region as enriched for 5hmC. 30 As the ICR1 is known to be enriched for 5mC, the H19 gene body is enriched for 5hmC and the GAPDH promoter is depleted for both modifications; 30 enrichment at these regions acted as positive and negative controls for each cytosine modification. Primer details are given in Table 1.…”
Section: Gene Expressionmentioning
confidence: 99%
“…28 5-hydroxymethylcytosine (5hmC) is a recently described cytosine modification that may be an intermediate in the DNA demethylation pathway 29 and is present in the placenta. 30 Since commonly used methods of assessing DNA methylation using bisulfite conversion do not discriminate between 5mC and 5hmC, 31 previous studies reporting altered DNA methylation at placental DMRs in association with fetal growth may be confounded. We used specific enrichment techniques to map 5mC and 5hmC at the DMRs controlling the expression of IGF2 and CDKN1C in human placenta, and additionally explored relationships between 5mC, 5hmC, gene expression, and fetal growth across the full range of normal birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…f CG methylation across promoters often varies greatly across a relatively narrow region with lowest methylation typically observed around the transcription start site (TSS), even in un-expressed genes CH sites and hydroxymethylation of CG sites are prevalent in several organ systems, particularly the central nervous system (Lister et al 2013;Kinde et al 2015). The high levels of hmCG and mCH in the brain stand in contrast to other organs (Nestor et al 2012) and suggest the possibility that the epigenomics of the aging brain is substantially different from other tissues (Masser et al 2017a). CG dinucleotides occur far less frequently (< 1% of dinucleotide pairs) than any other dinucleotide pairs (Bird 1980;Karlin and Mrázek 1997) and are clustered together in regions termed CG islands (Lander et al 2001).…”
Section: Nature and Regulation Of Dna Modificationsmentioning
confidence: 99%